Independent prognostic importance of blood urea nitrogen to albumin ratio in critically ill patients with congestive heart failure - Jingxiang Yang; Jiuyi Wang; Kai Wang (Scientific Reports)
Abstract New studies have revealed an association between chronic heart failure, the severity of septic shock, and the blood urea nitrogen to albumin ratio (BAR). Nevertheless, its role in congestive heart failure patients admitted to the intensive care unit remains unclear. This study aimed to investigate the association between BAR and mortality among these patients. The present study analyzed data from the MIMIC-IV (version 2.2) database, targeting patients with congestive heart failure. The study outcome was all-cause mortality within the first year after discharge. Patients were categorized into three groups—T1, T2, and T3—based on tertiles of BAR levels. To explore the relationship between BAR and mortality, Kaplan-Meier survival curves and multivariate Cox proportional hazards models, adjusted for potential confounders, were employed. Additionally, a dose-response relationship between BAR and mortality risk was evaluated using a restricted cubic spline model and threshold effect analysis. Subgroup analyses were conducted across diverse populations to assess the prognostic value of BAR. Furthermore, the predictive capabilities of blood urea nitrogen, albumin, blood urea nitrogen combined with albumin, and BAR were assessed through receiver operating characteristic analysis. The cohort comprised 4506 patients diagnosed with congestive heart failure. Kaplan-Meier curves revealed that all-cause mortality was significantly elevated in patients within the higher BAR tertiles (p < 0.001). Multivariate Cox regression analysis indicated that patients in the T2 (hazard ratio (HR): 1.20, 95% confidence interval (CI): 1.06 ~ 1.36) and T3 groups (HR: 1.37, 95% CI: 1.18 ~ 1.57) had a significant increase in mortality risk relative to the T1 group (p for linear trend < 0.001). Most subgroups showed this association, with the exception of variations of levels in creatinine, blood urea nitrogen, alkaline phosphatase, and alanine aminotransferase. Notably, the BAR demonstrated superior predictive accuracy for mortality compared to blood urea nitrogen or serum albumin alone, while exhibiting comparable performance to their combined measure. Among ICU patients with congestive heart failure, an elevated BAR was associated with an increased risk of all-cause 1-year mortality, particularly in those with less impaired liver and kidney function. Therefore, BAR may be measured to comprehensively evaluate the patients’ prognosis.